Prevalence of acid reflux in functional dyspepsia and its association with symptom profile. Issue 10 (21st June 2005) - Tack, J; Caenepeel, P; Arts, J; Lee, K-J; Sifrim, D; Janssens, J
Abstract : Aim: A subset of functional dyspepsia patients respond to acid suppressive therapy, but the prevalence of non-erosive reflux disease in functional dyspepsia and its relevance to symptoms have never been established. The aim of the present study was to study 24 hour pH monitoring in consecutive functional dyspepsia patients. Methods: A total of 247 patients with dyspeptic symptoms (166 women, mean age 44 (SEM 1) year), with a negative upper gastrointestinal endoscopy and without dominant symptoms of heartburn participated in the study. In all patients, the severity of dyspeptic symptoms and the presence of heartburn was assessed by a questionnaire and a 24 hour oesophageal pH monitoring study was performed. All patients underwent a gastric emptying breath test and in 113 a gastric barostat study was performed. Results: Abnormal pH monitoring (acid exposure >5% of time) was found in 58 patients (23%). Of 21 patients with a positive heartburn questionnaire, 76% had pathological pH monitoring, while this was the case in only 18.5% of patients with a negative heartburn questionnaire. Demographic characteristics and the prevalence of other pathophysiological mechanisms did not differ between heartburn negative patients with normal or abnormal acid exposure. Pathological acid exposure in heartburn negative patients was associated with the presence of epigastric pain (65 v 84%, p<0.005) and of moderate or severe pain (48 v 69%, p = 0.005). Conclusion: Pathological oesophageal acid exposure is only present in a subset of heartburn negative functional dyspepsia patients, which are characterised by a higher prevalence of epigastric pain.